A Performance Comparison Analysis of Solar Power Plants and Steam Power Plants in the Context of PT Rapp - Sidabalok, Tulus Roy Wanda; Harahap, Zen Maulana; Yudhi Ganda Sujatmiko; Lumbantobing, Yan Bastian; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
The growing emphasis on renewable energy and environmental sustainability has driven industries to explore cleaner energy sources. This study focuses on compairing the performance of Solar Power Plants(SPPs) and Steam Power Plants(SPPs) operated by PT Riau Andalan Pulp and Paper(PT RAPP) in Riau, Indonesia. The research utilized daily energy production records, environmental observations, and statistical analysis to assess the efficiency, reability, and sustainability of both systems. Results indicate thet Solar Power Plants are highly efficient in converting solar radiation into electricity but face operational challenges due to equipment malfunction, particularly in Phases On the other hand, Dual Fuel Line 2 Steam Power Plant demonstrated consistent performance, achieving a thermal efficiency of 43.24% by utilizing biomass as a primary fuel. Despite this, it still requires natural gas for operational stability. The study concludes with recommendations for enhancing solar power plant maintenance, expanding capacity, and investing in emission control technologies for steam plants. These steps aim to create a more sustainable and efficient energy ecosystem for PT RAPP, supporting its long-term energy needs and environmental goals.